Problems of Inclusive Learning in Fostering Entrepreneurial Motivation in Students with Disabilities: Systematic Literature Review (SLR) - Lestari, Ana Dwi Setyo; Jazuli; Murwani, F. Danardana; Wardana, Ludi Wishnu; Wati, Andy Prasetyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to investigate problems in inclusive learning for students with disabilities and their relationship with entrepreneurial motivation. The method used is Systematic Literature Review (SLR), collecting and analyzing relevant previous research. The results show various problems in the implementation of inclusive learning for students with disabilities, including lack of resources and training for teachers, and the existence of negative stereotypes. However, research has also found that effective inclusive learning can increase entrepreneurial motivation among learners with disabilities. These findings have important implications for the development of more effective and sustainable inclusive education policies. There needs to be efforts to improve accessibility, provide training for educators, and reduce stigma against students with disabilities. In addition, an emphasis on inclusive learning that encourages entrepreneurial motivation can help expand economic opportunities for individuals with disabilities, thereby supporting broader social inclusion.